Conversational Implicature Containing Sexist Humor in Deddy Corbuzier's Podhub with Vidi Aldiano, Ummi Quary and Wika Salim: Pragmatic Study - Puteri, Ariani Dwi (Universitas Teknokrat Indonesia, 2025)
In pragmatics, implicature is a branch of science that studies the meaning contained in an utterance. Implicatures provide an opportunity for speakers and interlocutors to have the widest possible relevance regarding what has been said. This research aims to focus on conversational implicatures, thereby describing (1) types of conversational implicatures containing sexist humor in Podhub Deddy Corbuzier, Vidi Aldiano with Ummi Quary and Wika Salim, (2) the implications that arise between conversational implicatures containing sexist humor in Podhub Deddy Corbuzier, Vidi Aldiano with Ummi Quary and Wika Salim. This research is a qualitative descriptive study using listening and note-taking techniques, after that it is analyzed using Paul Grice's theory of conversational implicature with Dell Hymes's conversational classification, after that it looks at the context of sexist humor using the theory of Shifman & Dafna (2010). Sexist humor often occurs because of inequality between men and women and is normalized. The results of this research obtained 21 conversational implicatures containing sexist humor, consisting of; 8 data imply insinuating, 4 data imply confirming, 3 data imply teasing, 2 data imply disappointment, 2 data imply displeasure, 1 data imply expecting and 1 data imply telling.